Pasture trees in tropical México: the effect of soil nutrients on seedling growth - Martínez-Sánchez, José Luis (Revista de Biología Tropical, 2006)
Environment and seedling community under isolated trees in pastures are different from those in the open pasture. The effect of the pasture trees on the soil nutrients and on the seedling growth were investigated. Seven isolated trees and eight plots were selected in two pastures of 12-yr and 32-yr old derived from a lowland rain forest with nutrient-rich soil at Los Tuxtlas, México. The soil concentrations of total N, P Bray, K+, Na+, Ca2+ and Mg2+, plus others physical and chemical characteristics, were compared between the pasture trees and the open -pasture. An experiment was done to test the hypothesis that soil from under the pasture trees was better for seedling growth than soil from the open pasture. Seedlings of two native tree species and two domesticated species were grown in soil from the two different sites in a shade-house. The dry weight of the shoot and root/shoot ratio were compared. Only total N, P and Na+ differed slightly in concentrations between the sites, but did not promote more seedling biomass. It seems that the soil at this location is sufficiently nutrient-rich even in the open pastures and over-ride any effect of the pasture trees on nutrient availability.